Innovation creation and adoption in the Malaysian construction industry: Research proposal - Mustafa Kamal, Ernawati; Yusof, Nor' Aini; Roosli, Ruhizal (2013)
The construction industry has been criticized because of its low productivity and quality in comparison with other industries.One of the main reasons for this situation is because the industry suffers from lack of innovation. However, research on innovation within an organisational setting has moved further to understand whether innovation is being adopted or being created because of the failure in many innovation efforts.The literatures strongly suggest different characteristics of the two innovations and each need a different skills, resources and culture to develop. This research sought to understand the fundamental characteristics of innovation creation and innovation adoption in construction industry; and develop a model classifying criteria for innovation creation and innovation adoption in the context of Malaysian construction industry. The research will employ both quantitative and qualitative methods for data collection.The results of this research will provide better uderstanding the characteristics of innovation creation and innovation adoption.The model classifying innovation creation and innovation adoption develop in the research will form a basis for the industry players to identity appropriate strategies and resources to encourage such innovations.